HISTORICAL DYNAMICS OF HINDU–MUSLIM RELATIONS IN PRE-COLONIAL BALI : A SOCIO-CULTURAL PERSPECTIVE - Erry Hendriawan; Anak Agung Ngurah Budiadnyana (UHN I Gusti Bagus Sugriwa Denpasar, 2026)
This study examines the historical dynamics of Hindu–Muslim relations in pre-colonial Bali, with particular attention to the late medieval and early modern period before sustained Dutch colonial intervention. Moving beyond conversion-centered and conflict-oriented narratives, the article asks how religious coexistence was practiced, regulated, and sustained within everyday social, economic, and political contexts. Employing a qualitative historical approach, the study analyzes indigenous narratives, travel accounts, early external records, and recent scholarly literature through source criticism and contextual interpretation. The findings show that Muslim communities were incorporated into Balinese society through maritime trade, service to local courts, diplomatic mediation, and localized cultural adaptation. Hindu political structures provided institutional space for religious diversity, while customary norms helped regulate interaction across religious boundaries. The phrase pragmatic accommodation is used here not to idealize pre-modern tolerance, but to describe historically situated arrangements in which communities preserved distinct religious identities while sharing markets, political obligations, and social spaces. Economic interdependence, royal pragmatism, and adat-based regulation emerged as the principal mechanisms shaping Hindu-Muslim relations. By foregrounding Bali as an active arena of interreligious engagement, this study contributes to broader historiographical debates on religious pluralism in Southeast Asia and offers historically grounded insights for contemporary discussions of social harmony in Indonesia